2021
DOI: 10.3390/cryst11080941
|View full text |Cite
|
Sign up to set email alerts
|

Residual Repeated Impact Strength of Concrete Exposed to Elevated Temperatures

Abstract: Portland cement concrete is known to have good fire resistance; however, its strength would be degraded after exposure to the temperatures of fire. Repeated low-velocity impacts are a type of probable accidental load in many types of structures. Although there is a rich body of literature on the residual mechanical properties of concrete after high temperature exposure, the residual repeated impact performance of concrete has still not been well explored. For this purpose, an experimental study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 94 publications
(117 reference statements)
1
11
0
Order By: Relevance
“…The mixes with high volume replacements of NA with RCA exhibited wider cracks, which might have been due to the effortless delamination of the newly formed mortar from the adhered mortar available on the surface of RCA due to its inferior quality. The specimens without steel fibres tended to split into pieces at the stage of failure [ 64 , 65 , 66 , 67 ], whereas the specimens incorporating steel fibres failed without splitting [ 68 , 69 , 70 , 71 ]. This is attributed to the bridging mechanism of steel fibres with the concrete, which improved the interlocking between the particles in the matrix [ 72 , 73 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The mixes with high volume replacements of NA with RCA exhibited wider cracks, which might have been due to the effortless delamination of the newly formed mortar from the adhered mortar available on the surface of RCA due to its inferior quality. The specimens without steel fibres tended to split into pieces at the stage of failure [ 64 , 65 , 66 , 67 ], whereas the specimens incorporating steel fibres failed without splitting [ 68 , 69 , 70 , 71 ]. This is attributed to the bridging mechanism of steel fibres with the concrete, which improved the interlocking between the particles in the matrix [ 72 , 73 ].…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…FRC is the potential for enhancing impact-resistant applications in essential constructions such as flooring, nuclear storage, and airplane pavements [5]. An intense explosion may not harm the buildings, but repeated collisions can cause damage and collapse [6]. Increasing made-made risks have forced the construction of high impact resistance infrastructure subjected to repeated crashes and explosions [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased Q1 and Q2 due to a higher fibre dose (2.4%) resulted in improved ductility. 6 11.1 6.7 16.9 9.0 11.5 9.7 9.4 7.5 13.5 6.6 13.0 6.0 15.0 10.1 9.9 6.9 11.5 5.9 16.6 9.0 13.8 8.9…”
mentioning
confidence: 99%
“…So far, extensive experimental research has been conducted on the mechanical properties and seismic performance of structural components after exposure to fire. Al-Ameri conducted an experimental study to evaluate the effect of high temperatures on mechanical properties and repeated impact strength of normal strength concrete [3]. The results revealed that the compressive strength was increased by less than 2% after exposure to 100 °C, while it reduced to approximately 50% of the original strength at 600 °C; the impact strength decreased sharply by 74.2% after exposure to 200 °C.…”
Section: Introductionmentioning
confidence: 99%